(untitled) (REVISTA SAYWA, 2023)
In December 2019, the fi rst cases of respiratory disease caused by an emerging coronavirus were detected, which was called SARS-CoV-2, which in the fi rst months of 2020 spread throughout the world, for which the World Organization of the health raised its status to pandemic. The disease, known as Covid-19, occurs with a cough, fever and respiratory distress. The most serious forms, which mainly affect the elderly and with certain comorbidities, are